Risk Factors of Chronic Energy Deficiency among Pregnant Women in Minahasa - Kairupan, Michelle; Manengkey, Olvin Kristin; Baithesda (Fakultas Ilmu Keperawatan Universitas Klabat, 2026)
Chronic Energy Deficiency (CED) remains a major public health concern among pregnant women and is associated with adverse maternal and neonatal outcomes. This study aimed to analyze the risk factors for CED and identify the dominant predictors among pregnant women in Minahasa. A cross-sectional analytical design was employed involving 246 pregnant women. Data were collected using structured questionnaires, dietary assessments, and Mid-Upper Arm Circumference (MUAC) measurements. Bivariate analysis was performed using the Chi-square test, and multivariate analysis was conducted using logistic regression. The prevalence of CED was 41.5%. Significant factors associated with CED included maternal age (p=0.012; OR=3.9), parity (p=0.004; OR=4.7), knowledge (p<0.001; OR=14.8), and dietary patterns (p=0.002; OR=2.9). Multivariate analysis revealed that maternal knowledge was the strongest predictor of CED (aOR=15.25; 95% CI: 3.80–61.20), followed by parity, age, and dietary diversity. Education and antenatal care (ANC) visits were not significantly associated with CED prevalence. These findings indicate that knowledge gaps and poor dietary diversity are key determinants of CED. Strengthening culturally sensitive nutrition education within antenatal care services is essential for improving maternal nutrition and supporting stunting reduction strategies. Defisiensi Energi Kronis (CED) tetap menjadi masalah kesehatan masyarakat yang serius di kalangan ibu hamil dan dikaitkan dengan hasil kehamilan yang buruk bagi ibu dan bayi baru lahir. Penelitian ini bertujuan untuk menganalisis faktor risiko CED dan mengidentifikasi prediktor utama di kalangan ibu hamil di Minahasa. Desain penelitian analitik cross-sectional digunakan dengan melibatkan 246 ibu hamil. Data dikumpulkan menggunakan kuesioner terstruktur, penilaian pola makan, dan pengukuran Lingkar Lengan Atas Tengah (MUAC). Analisis bivariat dilakukan menggunakan uji Chi-square, sedangkan analisis multivariat dilakukan menggunakan regresi logistik. Prevalensi CED sebesar 41,5%. Faktor-faktor signifikan yang terkait dengan CED meliputi usia ibu (p=0,012; OR=3,9), paritas (p=0,004; OR=4,7), pengetahuan (p<0,001; OR=14,8), dan pola makan (p=0,002; OR=2,9). Analisis multivariat menunjukkan bahwa pengetahuan ibu merupakan prediktor terkuat CED (aOR=15,25; 95% CI: 3,80–61,20), diikuti oleh paritas, usia, dan keragaman makanan. Pendidikan dan kunjungan perawatan antenatal (ANC) tidak secara signifikan terkait dengan CED. Temuan ini menunjukkan bahwa kesenjangan pengetahuan dan keragaman pola makan yang buruk merupakan faktor penentu utama CED. Memperkuat pendidikan gizi yang sensitif terhadap budaya dalam layanan perawatan antenatal sangat penting untuk meningkatkan gizi ibu dan mendukung strategi pengurangan stunting.